2022
DOI: 10.3390/su15010201
|View full text |Cite
|
Sign up to set email alerts
|

Health and Safety Improvement through Industrial Revolution 4.0: Malaysian Construction Industry Case

Abstract: Safety on construction sites is now a top priority for the construction industry all around the world. Construction labor is often seen as hazardous, putting employees at risk of serious accidents and diseases. The use of Industrial Revolution (IR) 4.0 advanced technologies such as robotics and automation, building information modelling (BIM), augmented reality and virtualization, and wireless monitoring and sensors are seen to be an effective way to improve the health and safety of construction workers at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 82 publications
0
18
0
1
Order By: Relevance
“…Based on the feedback received, the respondents agreed with most of the SWOT factors on the selected sustainable stormwater practices, including the green roof, rain garden/bioretention system, and porous pavement. The correlation analysis showed that the green roof, rain garden/bioretention system, and porous pavement have a strong positive relationship for the Strength and Opportunity factors, with the r-values for most relationships being close to one (1), which are statistically significant, with a p-value of less than 0.05. The selected sustainable stormwater practices also showed a weak positive relationship for the Weakness and Threat factors, with the r-values for most relationships close to zero (0), which are not statistically significant, with a p-value of more than 0.05.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Based on the feedback received, the respondents agreed with most of the SWOT factors on the selected sustainable stormwater practices, including the green roof, rain garden/bioretention system, and porous pavement. The correlation analysis showed that the green roof, rain garden/bioretention system, and porous pavement have a strong positive relationship for the Strength and Opportunity factors, with the r-values for most relationships being close to one (1), which are statistically significant, with a p-value of less than 0.05. The selected sustainable stormwater practices also showed a weak positive relationship for the Weakness and Threat factors, with the r-values for most relationships close to zero (0), which are not statistically significant, with a p-value of more than 0.05.…”
Section: Discussionmentioning
confidence: 95%
“…Massive development since the Industrial Revolution (IR) has progressed rapidly in many countries [1,2]. Even though the IR showed an impressive achievement in terms of economy and poverty alleviation, it also contributed some negative outcomes, especially to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…BIM and integrated systems have the highest potential as advanced technologies which can be applied to lessen the barriers to the benefits of implementing OHSMSs in the construction industry. When introducing BIM in the construction industry, it must be prioritised to enhance safety and health performance [150]. Therefore, understanding the barriers to the implementation of OHMSMSs and their associated benefits is needed to facilitate the adoption of OHSMSs.…”
Section: Other Ohsms Elements In the Construction Industrymentioning
confidence: 99%
“…At the heart of this transformation lies the integration of data-driven technologies, giving rise to Construction 4.0 and Construction 5.0 (Forcael et al, 2020;Perrier et al, 2020;Marinelli, 2023;Chen et al, 2022; ). These innovative approaches not only enhance construction processes but also align with the broader vision of Society 5.0, where technology empowers a human-centric society (Skobelev et al, 2017;Cook, 2021;Musarat, et al, 2023). This section delves into the intricacies of data-driven technologies in construction, tracing their evolution from Construction 4.0 to Construction 5.0 and their profound impact on Society 5.0.…”
Section: Introductionmentioning
confidence: 97%
“…Known as Construction 4.0, the current AEC landscape is witnessing a convergence of digital innovations, shaping smart and sustainable construction practices (Sawhney et al, 2020;Forcael et al, 2020;Perrier et al, 2020). Additionally, the shift towards Construction 5.0 and Society 5.0 highlights the importance of societal well-being, advocating for a holistic approach that combines technological advancements with human-centric development (Yitmen et al, 2023;Marinelli, 2023;Chen et al, 2022;Musarat et al, 2023;Liu et al, 2022). In the pursuit of smart and sustainable construction, this study highlights the crucial role of data-driven technologies, particularly IoT, computing models, and big data solutions.…”
Section: Introductionmentioning
confidence: 99%